Online Task-Based Language Teaching and Face-to-Face TBLT Utilizing SIKOLA in Writing Class: How does It Affect EFL Students’ Writing Performance and Attitude? - Marleiny Radjuni (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
The purpose of this research is to investigate the online task-based language teaching (TBLT) and face-to-face learning affects EFL learners' writing performance and attitude. The study focused on the application TBLT in teaching writing using two methods: online learning with SIKOLA platform and face-to-face learning which had only recently been developed. This research used mixed-methods. This study included one class of twenty-four undergraduate students (aged 19-21). Students were asked to complete the tasks online and face-to-face using the LMS SIKOLA, which has been used throughout the semesters at the university. The study discovered that students had positive attitudes toward the use of online task-based language teaching in terms of providing better drafts and revision. The study also discovered that there was a strong understanding of the procedures for carrying out the task-based assessments. In other words, they found out themselves that these methods can improve their performance in writing such as writing better drafts and revisions. The findings will help EFL students understand the procedures of online TBLT and face-to-face TBLT strategies in writing classes. Learners are encouraged to actively participate in both online and face-to-face learning discussions.